Orientasi Penilaian dan Sistem Penilaian Prestasi Kerja - Deti Deti; Nazwa Anzani; Anggi Widya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The role of appraisal orientation and work performance appraisal systems in human resource management is very important to motivate employees and achieve company goals. This article uses a qualitative approach with case studies to explore employee performance and working conditions. The research results show that integration between appraisal orientation and a work performance appraisal system that is tailored to the company's needs can support organizational growth and increase employee motivation. Appraisals and work performance appraisal systems are recognized as effective tools in creating excellence for companies by directing the achievement of organizational goals and improving employee performance. In this context, this research highlights the importance of using relevant and transparent evaluation methods to ensure fairness in employee appraisals. Therefore, implementing good work performance appraisals also involves open communication between management and employees, as well as providing constructive feedback. Thus, this article emphasizes that job performance appraisal is not only an evaluation tool, but also a strategic instrument for building a work culture that supports employee growth and development as well as overall organizational success.